Evaluación de la calidad del agua para riego en las épocas seca y lluviosa de los canales Alumis, Norte, Jiménez Cevallos, Belisario Quevedo, La Martínez y el río San Juan de Patoa, ubicados en la provincia de Cotopaxi, período 2021-2022. - Cuvi Vásquez, Manuel Antonio (2022)
Water resources are fundamental to guarantee optimal food security; agriculture requires large quantities of water, including quality water, for its different production processes and is essential for sustainable management. This research was carried out during the dry and rainy hydrological seasons, during which the quality of the water resources entering the Jiménez Cevallos (P1), Norte (P2), Alumís (P3), Martínez (P5), and Belisario Quevedo (P6) irrigation canals, as well as El Rio Patoa (P4) that feeds the three reservoirs of the San Juan project, was evaluated. For this purpose, the following indexes were applied: CCME_WQI, taking as a reference the thresholds established by the Ecuadorian regulation of AM 097-A; Wilcox diagram, considering the RAS normal and EC; Percentage of Soluble Sodium (PSS); Residual Sodium Carbonate (CSR) and the Permeability Index (PI). According to results achieved in the research, it was determined that the water quality for the dry season at points: P1, P2, P3, P4, and P5 present a water resource of excellent quality, except for P6, which receives water of good quality due to the non-compliance of the Cr+6 parameter (0.2>0.1 mg/L). In contrast, for the rainy season points: P2, P3, P5, and P6 remain in the excellent category; P4 shows a good quality due to the non-compliance of the parameters: Fe (8.2>5 mg/L), As (0.12>0.1 mg/L) and Al (6.82>5 mg/L), P1 captures water resource of poor quality, because of the magnitude in the concentration of fecal Coliforms (460 000>1000 NMP/100ml). According to the Wilcox diagram classification, the dry season reflects in points: P3, P4, P5, and P6 a C1- S1 classification, except points P1 and P2 present a C2-S1 classification. The rainy season maintains P3, P5, and P6 with a C1-S1 classification: P3, P5, and P6 in the C1-S1 category. On the other hand, point P4 is located in the C2-S1 classification, and in turn, points P1 and P2 remain in the same categorization. The results of the PSS indicate that the dry season presents a questionable water quality at point P2, while the rainy season reflects well to acceptable water quality in the water bodies. The CSR for the dry season indicates more critical values at points P1 and P3 that condition its use due to the problems it causes in the soil structure, as well as point P2 that presents a quality not recommended for its use, while the rainy season indicates a conditioned use at points P4 and P6. The permeability index did not reflect any water body in class III in both seasons. The quality of irrigation water depends mainly on the total concentration of dissolved constituents, indicating that the water is suitable for irrigation as long as sodium and salinity tolerant crops are used.